2023
DOI: 10.5114/aoms/171473
|View full text |Cite
|
Sign up to set email alerts
|

Association between electronic nicotine delivery systems use and risk of stroke: a meta-analysis of 1,024,401 participants

Kamal Awad,
Maged Mohammed,
Seth S. Martin
et al.

Abstract: IntroductionTo evaluate the relationship between electronic nicotine delivery systems (ENDS) use and the risk of stroke when compared to non-smokers.Material and methodsA comprehensive search was conducted until June 15, 2023. We included observational studies that assessed association of current or former usage of ENDS with risk of stroke compared with non-smokers, reported the risk estimate as odds ratio (OR) or hazard ratio (HR) and were adjusted for possible confounders.Results6 studies with 1,024,401 part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Similarly, heavy alcohol consumption was associated with an increased risk of stroke, whereas light-moderate alcohol intake was associated with a decreased risk of stroke ( 10 ). Smoking or electronic nicotine delivery systems use have also been shown to be associated with the risk of stroke ( 40 , 41 ), although the association between serum nicotine levels and the risk of stroke remains unclear. Physical activity, on the other hand, is recognized as an effective means in stroke prevention ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, heavy alcohol consumption was associated with an increased risk of stroke, whereas light-moderate alcohol intake was associated with a decreased risk of stroke ( 10 ). Smoking or electronic nicotine delivery systems use have also been shown to be associated with the risk of stroke ( 40 , 41 ), although the association between serum nicotine levels and the risk of stroke remains unclear. Physical activity, on the other hand, is recognized as an effective means in stroke prevention ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…Awad et al conducted a meta-analysis that aimed to assess the relationship between EC usage and the risk of stroke in comparison to non-smokers. The authors reported that usage was significantly associated with an increased risk of stroke (OR: 1.52) when compared with non-users [ 51 ].…”
Section: Reviewmentioning
confidence: 99%
“…A meta-analysis in August 2023 comprising 1024401 subjects confirmed increased stroke risk of roughly >50% in active ENDS users in comparison to non-users, purportedly due to collective effects of blood-brain barrier damage, blood pressure elevation, vascular repair impairment, endothelial dysfunction, and platelet activation. Since no such association was obtained for people who were not actively vaping, it was emphasized that smoking cessation is a linchpin for preventing stroke [ 84 ]. Concerning toxicity from individual components, the American Heart Association (AHA) implicated cardiac remodeling and arrhythmogenesis as a long-term consequence of nicotine use.…”
Section: Reviewmentioning
confidence: 99%